Comparison of Targeted Mass Spectrometry Techniques with an Immunoassay: A Case Study for HSP90α. Issue 1 (30th October 2017) - Güzel, Coşkun; Govorukhina, Natalia I.; Stingl, Christoph; Dekker, Lennard J. M.; Boichenko, Alexander; van der Zee, Ate G. J.; Bischoff, Rainer P.H.; Luider, Theo M.
Abstract : Purpose: The objective of this study is to better understand factors governing the variability and sensitivity in SRM and PRM, compared to immunoassay. Experimental design: A 2D‐LC–MS/MS‐based SRM and PRM assay is developed for quantitative measurements of HSP90α in serum. Forty‐three control sera are compared by SRM, PRM, and ELISA following the manufacturer's instructions. Serum samples are trypsin‐digested and fractionated by strong cation exchange chromatography prior to SRM and PRM measurements. Analytical parameters such as linearity, LOD, LOQ, repeatability, and reproducibility of the SRM, PRM, and ELISA are determined. Results: PRM data obtained by high‐resolution MS correlate better with ELISA measurements than SRM data measured on a triple quadrupole mass spectrometer. While all three methods (SRM, PRM, and ELISA) are able to quantify HSP90α in serum at the ng mL –1 level, the use of PRM on a high‐resolution mass spectrometer reduces variation and shows comparable sensitivity to immunoassay. Conclusions and clinical relevance: Using fractionation, it is possible to measure ng mL –1 levels of HSP90α in a reproducible, selective, and sensitive way using PRM in serum. This opens up the possibility to use PRM in a multiplexed way as an attractive alternative for immunoassays without the use of antibodies or comparable binders.